THE ASSESSMENT OF SUAEDA FRUTICOSA AND HELIOTROPIUM CURASSAVICUM L COMPARATIVE AND COMBINED ANTIOXIDANT POTENTIAL (Journal of Medical & Health Sciences Review, 2025)
The primary causes of cancer include lifestyle, environment, and genetic defects. Herbal treatment is essential for preventing cancer from proliferating and metastasizing. Heliotropium thcurassavicum L. a member of the Boraginaceae family and a perennial shrub, and Suaeda fruticosa, has a capacity to control the formation of many different kinds of free radicals, which can react with proteins, lipids, and DNA to cause cancer and other chronic diseases.We performed antioxidant activity to find out the Suaeda fruticosa and Heliotropium thcurassavicum L antioxidant potential using DPPH free radicals assay. We found that scavenging capacity of Suaeda fruticosa was 15%, 29%, and 43%. The Heliotropium thcurassavicum L antioxidant potential was 25%, 37%, and 55%. Next we examined the combined antioxidant potential of both plant extract which showed the 40%, 61%, and 75%, respectively.Our results demonstrated that the combined antioxidant potential of Suaeda fruticosa and Heliotropium thcurassavicum L has more significant result than individual plant extracts.